2019
DOI: 10.1002/glia.23721
|View full text |Cite
|
Sign up to set email alerts
|

NG2 glia are required for maintaining microglia homeostatic state

Abstract: Microglia play vital roles in the health and diseases of the central nervous system. Loss of microglia homeostatic state is a key feature of brain aging and neurodegeneration. However, the mechanisms underlying the maintenance of distinct microglia cellular states are largely unclear. Here, we show that NG2 glia, also known as oligodendrocyte precursor cells, are essential for maintaining the homeostatic microglia state. We developed a highly efficient and selective NG2 glia depletion method using small‐molecu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
81
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(86 citation statements)
references
References 31 publications
5
81
0
Order By: Relevance
“…One of the factors could be the OPCs in the white matter, as Liu et al recently discovered that selective OPC depletion using small-molecule inhibitors of platelet-derived growth factor (PDGF) signaling abolished the homeostatic microglia signature but did not change their disease-associated profiles in cultured brain slices. 77 Similar findings were also observed in vivo by inducing conditional depletion of OPCs in adult mouse brain, suggesting that OPC has a crucial influence onto cellular states of microglia which are relevant to neurodegenerative diseases. Although a small population of OPCs exists in the gray matter as well, 78 they are reported to be mostly quiescent or slowly proliferating, 79 whereas OPCs in white matter continuously generate mature and myelinating oligodendrocytes in response to PDGF signaling, 79,80 showing that OPCs have different characteristics depending on its region.…”
Section: Crog Lial Ac Tivit Y In White Vs G R Ay Mat Tersupporting
confidence: 58%
See 1 more Smart Citation
“…One of the factors could be the OPCs in the white matter, as Liu et al recently discovered that selective OPC depletion using small-molecule inhibitors of platelet-derived growth factor (PDGF) signaling abolished the homeostatic microglia signature but did not change their disease-associated profiles in cultured brain slices. 77 Similar findings were also observed in vivo by inducing conditional depletion of OPCs in adult mouse brain, suggesting that OPC has a crucial influence onto cellular states of microglia which are relevant to neurodegenerative diseases. Although a small population of OPCs exists in the gray matter as well, 78 they are reported to be mostly quiescent or slowly proliferating, 79 whereas OPCs in white matter continuously generate mature and myelinating oligodendrocytes in response to PDGF signaling, 79,80 showing that OPCs have different characteristics depending on its region.…”
Section: Crog Lial Ac Tivit Y In White Vs G R Ay Mat Tersupporting
confidence: 58%
“…Although there may be different mechanisms involved between macrophages and microglia, the finding suggests the existence of white matter‐specific factors that can boost the phagocytic activity. One of the factors could be the OPCs in the white matter, as Liu et al recently discovered that selective OPC depletion using small‐molecule inhibitors of platelet‐derived growth factor (PDGF) signaling abolished the homeostatic microglia signature but did not change their disease‐associated profiles in cultured brain slices . Similar findings were also observed in vivo by inducing conditional depletion of OPCs in adult mouse brain, suggesting that OPC has a crucial influence onto cellular states of microglia which are relevant to neurodegenerative diseases.…”
Section: Microglial Activity In White Vs Gray Mattermentioning
confidence: 75%
“…Expression of Cre-inducible iDTR in NG2-expressing cells has allowed for the targeted induction of cell death in OPCs following DT administration ( Figure 1 ; Birey et al, 2015 ; Zhang S.-Z. et al, 2019 ; Liu and Aguzzi, 2020 ). By this method, tissue-specific ablation of OPCs in the mouse prefrontal cortex was achieved by delivering DT via a cannula implanted into the targeted brain region, with the result of causing depressive-like behaviors, indicated by reduced open field activity (Birey et al, 2015 ).…”
Section: Genetic Technologiesmentioning
confidence: 99%
“…Similar studies, again using DT-mediated ablation of NG2-expressing cells, have provided the first indications of a role of OPCs in the maintenance of brain immune homeostasis and, while it has been known for some time that microglia can regulate the behavior and differentiation of OPCs (reviewed by Domingues et al, 2016 ), these studies have shown that OPCs can, in turn, modulate microglia (Zhang S.-Z. et al, 2019 ; Liu and Aguzzi, 2020 ; Marsters et al, 2020 ; Mecha et al, 2020 ). In the absence of NG2-positive OPCs, microglia become hypersensitive to lipopolysaccharide (LPS) injection, resulting in microglial activation and neuroinflammation (Zhang S.-Z.…”
Section: Genetic Technologiesmentioning
confidence: 99%
“…In addition to serving as progenitors of myelinating oligodendrocytes (18,19), NG2+ cells have unique properties, rendering them particularly interesting in the context of stress and EA. These properties include the ability to establish synaptic contacts with neurons (20)(21)(22)(23), to communicate with microglia (24) and to modulate glutamatergic signal transduction via the shed version of the NG2 ectodomain (25).…”
Section: Main Text Introductionmentioning
confidence: 99%